Diagnostic added value of interictal magnetic source imaging in presurgical evaluation of persons with epilepsy: A prospective blinded study. (10th July 2021) - Tripathi, Manjari; Kaur, Kirandeep; Ramanujam, Bhargavi; Viswanathan, Vibhin; Bharti, Kamal; Singh, Gaurav; Singh, Vivek; Garg, Ajay; Bal, Chandra Sekhar; Tripathi, Madhavi; Sharma, Mehar Chand; Pandey, Ravindra; et al.
Abstract: Background and purpose: In presurgical evaluation for epilepsy surgery, information is sourced from various imaging modalities to accurately localize the epileptogenic zone. Magnetoencephalography (MEG) is a newer noninvasive technique for localization. However, there is limited literature to evaluate if MEG provides additional advantage over the conventional imaging modalities in clinical decision making. The objective of this study was to assess the diagnostic added value of MEG in decision making before epilepsy surgery. Method: This was a prospective observational study. Patients underwent 3 h of recording in a MEG scanner, and the resulting localizations were compared with other complimentary investigations. Added value of MEG (considered separately from high‐density electroencephalography) was defined as the frequency of cases in which (i) the information provided by magnetic source imaging (MSI) avoided implantation of intracranial electrodes and the patient was directly cleared for surgery, and (ii) MSI indicated additional substrates for implantation of intracranial electrodes. Postoperative seizure freedom was used as the diagnostic reference by which to measure the localizing accuracy of MSI. Results: A total of 102 patients underwent epilepsy surgery. MEG provided nonredundant information, which contributed to deciding the course of surgery in 33% of the patients, and prevented intracranial recordings in 19%. A total of 76% of the patients underwent surgical resection in sublobes concordant with MSI localization, and the diagnostic odds ratio for good (Engel I) outcome in these patients was 2.3 (95% confidence interval 0.68, 7.86; p = 0.183) after long‐term follow‐up of 36 months. Conclusion: Magnetic source imaging yields additional useful information which can significantly alter as well as improve the surgical strategy for persons with epilepsy.